Implementation of Web-Based Payroll and Attendance System for Effective Employee Management at Bismika Tani Store - Wuryantono, Dhanang; Jazuli, Ahmad; Fiati, Rina (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Efficiency in managing employee attendance and payroll is crucial for a company's operations. Many businesses still use manual methods, leading to errors, payroll delays, and a lack of data transparency. This study develops a web-based payroll and attendance a system using the waterfall development approach, ensuring flexibility in feature adjustments. The system offers real-time attendance recording with location and photo verification, automated payroll calculations, and comprehensive reporting for management access. Built with PHP Native for the backend and a responsive UI, it enhances user experience. The Waterfall approach allows iterative development to meet operational needs at Bismika Tani Store. Testing shows a 75% reduction in recording errors and a 40% faster payroll process. Real-time reporting improves data transparency, facilitating better attendance and payroll monitoring. This system provides an effective solution for optimizing human resource management and boosting employee productivity at Bismika Tani Store. AbstrakAbsensi dan penggajian sangat penting bagi operasional perusahaan. Banyak bisnis masih menggunakan metode manual, yang menyebabkan kesalahan pencatatan, keterlambatan penggajian, dan kurangnya transparansi data. Penelitian ini mengembangkan sistem absensi dan penggajian berbasis web dengan pendekatan Waterfall Development, memastikan fleksibilitas dalam penyesuaian fitur. Sistem ini menawarkan pencatatan absensi real-time dengan verifikasi lokasi dan foto, perhitungan gaji otomatis, serta pelaporan komprehensif untuk akses manajemen. Dibangun dengan PHP Native untuk backend dan antarmuka pengguna yang responsif, sistem ini meningkatkan pengalaman pengguna. Pendekatan Waterfall memungkinkan pengembangan iteratif untuk memenuhi kebutuhan operasional di Bismika Tani Store. Pengujian menunjukkan pengurangan kesalahan pencatatan hingga 75% dan proses penggajian 40% lebih cepat. Pelaporan real-time meningkatkan transparansi data, mempermudah pemantauan absensi dan penggajian. Sistem ini menjadi solusi efektif untuk mengoptimalkan manajemen sumber daya manusia dan meningkatkan produktivitas karyawan di Bismika Tani Store.Kata kunci: Efisiensi administrasi; Otomatisasi; Absensi; Transparansi data; Manajemen karyawan.